A vida como obra de arte: entrelaçamentos entre ética e estética da existência no momento socrático-platônico segundo Michel Foucault - Pires Neto, Luiz de Camargo (2013)
This work aims investigate the entanglements between ethics and aesthetics of existence in the writings of Michel Foucault in which the philosopher studies what he called socratic-platonic moment . Based on the research presented by the philosopher in the course taught in 1982, named The hermeneutics of the subject, the present study departs from an analysis of the notion self care around two famous characters of the Antiquity: Socrate and Alcibíades, to indicate the possibility of a life as a work of art. Divided into four chapters, this analysis indicates a contextualisation of ethical reflection on Foucault s philosophical trajectory, exposes entanglements between epiméleia heautoû (self care) and gnôthi seautón (self-knowledge), philosophy and spirituality, presents the self care in the platonic dialogues and expresses the possibility of reusing the philosophy of the Ancients for the present moment